AWS certified cloud practitioner exam guide : build your cloud computing knowledge and upskill yourself as an AWS certified Cloud Practitioner (CLF-C01) /: build your cloud computing knowledge and upskill yourself as an AWS certified Cloud Practitioner (CLF-C01). (2021) - Daswani, Rajesh
No abstract available